Eroding Traditional Institutions and the Escalation of Banditry in Nupe Communities - Idrees Gana, Mahmud; Adeleye Oluwaseyi, Wisdom; Ogaji Adamu , Tijani; Yahaya, Liman (Universitas Airlangga, 2025)
Abstract The rise of banditry in rural Nigeria has attracted significant attention, yet limited empirical research has examined the role of traditional institutions in shaping local security outcomes. This study explores the relationship between the decline of traditional institutions and the escalation of banditry in Nupe communities, specifically focusing on Pategi and Lafiagi in Kwara State. Guided by functionalism theory, the study conceptualizes traditional institutions as essential components of community stability. Their weakening disrupts social regulation and creates governance gaps that are exploitable by criminal actors. A survey research design was employed, utilizing structured questionnaires administered online to 136 respondents. Data were analyzed using descriptive statistics and analysis of variance (ANOVA) with SPSS version 23. The results indicate a statistically significant association between the perceived erosion of traditional authority and the increased incidence of banditry, leading to the rejection of the null hypotheses. While traditional rulers still enjoy substantial community trust, their ability to manage conflicts and contribute to security has diminished. This study makes an empirical contribution by demonstrating that the decline of local institutions is a critical factor in rural insecurity, in addition to commonly cited economic and policing deficiencies. It concludes that revitalizing traditional institutions within hybrid security governance frameworks can strengthen community-based responses to banditry. Keywords: traditional institutions; banditry; nupe communities; pategi; lafiagi Abstrak Meningkatnya tindak perampokan di pedesaan Nigeria telah menarik perhatian yang signifikan, namun penelitian empiris yang membahas peran lembaga tradisional dalam membentuk hasil keamanan lokal masih terbatas. Penelitian ini mengkaji hubungan antara kemunduran lembaga tradisional dan eskalasi tindak perampokan di komunitas Nupe, dengan fokus khusus pada Pategi dan Lafiagi di Provinsi Kwara. Berdasarkan teori fungsionalisme, penelitian ini memandang lembaga tradisional sebagai komponen penting dalam stabilitas komunitas. Pelemahan lembaga tersebut mengganggu pengaturan sosial dan menciptakan celah dalam pemerintahan yang dapat dieksploitasi oleh aktor kriminal. Desain penelitian survei digunakan, dengan menyebarkan kuesioner terstruktur secara online kepada 136 responden. Data dianalisis menggunakan statistik deskriptif dan analisis varians (ANOVA) dengan SPSS versi 23. Hasil penelitian menunjukkan adanya hubungan yang signifikan secara statistik antara erosi wewenang tradisional yang dirasakan dan meningkatnya insiden perampokan, yang mengarah pada penolakan hipotesis nol yang relevan. Meskipun pemimpin tradisional masih mendapatkan kepercayaan yang besar dari komunitas, kemampuan mereka untuk mengelola konflik dan berkontribusi pada keamanan telah berkurang. Penelitian ini memberikan kontribusi empiris dengan menunjukkan bahwa kemunduran lembaga lokal merupakan faktor penting dalam ketidakamanan pedesaan, selain kekurangan ekonomi dan kekurangan dalam kepolisian yang sering dikemukakan. Penelitian ini menyimpulkan bahwa revitalisasi lembaga tradisional dalam kerangka pemerintahan keamanan dapat memperkuat respons berbasis komunitas terhadap perampokan. Kata kunci: lembaga tradisional; perampokan; komunitas nupe; pategi; lafiagi